Cd2SeCl2O9: Synthesis and Characterization of Novel Selinite-Chlorate Material - Ajaz, Humayun; Rabbani, Faiz; Naz, Narjis; Aslam Bhatti, Khurshid; Ahmad Ansari, Zameer (Asian Journal of Chemistry, 2013)
The white crystalline material Cd2SeCl2O9 was obtained by the solid state reaction of CdCl2 with SeO2 at 450 ºC and showed a distinct X-ray powder pattern. Elemental analysis was carried out by energy dispersive X-ray spectroscopy which confirmed the presence and ratio of the constituting elements. Decomposition temperature (527 ºC) of the product and its thermal behavior were investigated by the help of differential scanning calorimetry, whereas Fourier transform infra-red spectroscopy indicated the presence of SeO32- and ClO3– groups in the structure. Magnetic analysis proved the material to be ferromagnetic in nature.